Socio-economic factors associated with knowledge, attitudes, and practices response to the 2019 novel coronavirus (COVID-19) and preventive measures of COVID-19 in South Africa: An internet based cross-sectional study - Orrie, Naadiya (Department of Public Health and Family Medicine, 2024)
As part of a comprehensive response for COVID-19 prevention and control, South Africa, as well as many other countries, implemented extensive health and hygiene interventions to curb the spread of the disease. Extensive educational campaigns on all social media platforms as well as government agencies have been implemented in South Africa, however, adherence to these interventions, is affected by people's knowledge, attitude, and practice (KAP) as well as the economic status for the given information to be effective. This KAP study was to examine changes in knowledge, attitudes and practices and socio-economic factors associated with the knowledge, attitude, and practice response to the 2019 novel coronavirus (COVID-19) and preventive measures of COVID-19 in South Africa: an internet-based cross-sectional study. Surveys in Egypt, Pakistan, Saudi Arabia, Malaysia, Vietnam, Jordan, Pakistan, China, Iran, Bangladesh, and Uganda revealed that most respondents had a good knowledge of COVID19. Methods The study used an analytical cross-sectional design, and it was conducted in South Africa. At the time of the study, it was impossible to do community-based surveys due to the COVID-19 pandemic, hence, data was collected online. Data was collected using an online electronic survey where participants completed the online questionnaire once. The survey was drawn up using REDCap software. The KAP results were analyzed as proportions and then the association between KAP and demographic characteristics was done using ordered logit regression models for knowledge, attitude, and practice scores. Results Of the 188 study participants, majority were females (57%) and about (43%) were males. For age and income, the means and standard deviations were [(36.84;10.89) & (R13 344.50; R14 765.23)]. A greater proportion of the participants resided in formal residents (74%), had at least attained matric education (74%), also resided in the Western Cape province (97%) and were employed full time (60%). Income was a significant predictor of knowledge and practices with a unit increase in income increasing the ordered log-odds scale of knowledge by 5.13, while reducing ordered log-odds (OLO) scale for practices by 1.28. While a unit increase in age increased the OLO of knowledge (0.02), attitudes (0.02) and practices (0.03). Having matric education increased the OLO of knowledge (0.75) and practices (1.06) compared to participants with less than grade 11 education, while for attitudes it reduced the OLO of attitudes by 1.12. Additionally, staying in an informal house reduced the OLO of knowledge (15.55), attitudes (0.08) and practices (44.97) compared to staying in flat or house. However, having access to water [knowledge (16.40) and practices (30.31)] and electricity [knowledge (1.80) and practices (49.96)] increased the OLO of knowledge and practices compared to not having access. While being full-time and part-time employed increased the OLO of attitudes and practices [full-time; attitudes(1.16) & practices (1.57)] ; [part-time; attitudes(0.25) & practices (0.44)]. Lastly, staying in formal residence area increased the OLO of knowledge (0.21), attitudes (1.67) and practices (0.02), compared to staying in informal residences. Regarding the knowledge dimension participants showed that they were knowledgeable [(65%;Good knowledge), (9%;Fair knowledge), (26%;Poor knowledge)]. While for attitudes participants generally reported poor attitudes [42%;(Poor attitudes), (35%;Fair attitudes) (23%;Good attitudes)]. Lastly, participants had fairly good practices [(62%;Good practices), (13%; Fair practices), (25%;Poor practices)]. Conclusion This study showed significantly higher proportions of people with good knowledge and good practices, however, it also recorded a greater proportion of the participants who had poor attitudes. This information would be useful in the formulation of policy for community projects addressing behavioural change and adds to the global data on the same subject. The personal responsibility narrative was used during the pandemic, however people found it difficult to adhere to lockdown restrictions thus multipronged action will be needed to address the factors that affect KAP.